2022
DOI: 10.1097/ta.0000000000003543
|View full text |Cite
|
Sign up to set email alerts
|

Life threat during assaultive trauma: Critical posttraumatic stress disorder risk factors for injured patients

Abstract: This activity has been planned and implemented in accordance with the accreditation requirements and policies of the Accreditation Council for Continuing Medical Education (ACCME) through the joint providership of the American College of Surgeons and American Association for the Surgery of Trauma. The American College of Surgeons is accredited by the ACCME to provide continuing medical 2021 AAST QUICK SHOT 848

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Due to rapid developments in the modern world, long-term, persistent mental and environmental stresses affect the physical and mental health of millions of people globally. Appropriate stress can increase the body's ability to adapt and cope with environmental changes [1]; however, excessive or persistent stress can cause acute or chronic organ dysfunction and metabolic disorders [2]. Many studies [3][4][5] have found that long-term persistent stress can lead to many neuropsychiatric disorders, such as anxiety, depression, epilepsy, schizophrenia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to rapid developments in the modern world, long-term, persistent mental and environmental stresses affect the physical and mental health of millions of people globally. Appropriate stress can increase the body's ability to adapt and cope with environmental changes [1]; however, excessive or persistent stress can cause acute or chronic organ dysfunction and metabolic disorders [2]. Many studies [3][4][5] have found that long-term persistent stress can lead to many neuropsychiatric disorders, such as anxiety, depression, epilepsy, schizophrenia, etc.…”
Section: Introductionmentioning
confidence: 99%